WAYS OF ACTIVATING PSYCHOLOGICAL RESOURCES AND DEVELOPMENT SKILLS IN THE CONTEXT OF POSITIVE PSYCHOTHERAPY - Ayvazyan Մարինե (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
The article examines the possibilities of activating and developing psychological resources in the context of the theoretical approach of positive psychotherapy. The focus of the analysis is on the primary (innate) and secondary (acquired) abilities of the individual, which are considered as the main mechanisms for ensuring self-realization, adaptability and mental stability. The theoretical analysis presented in the article is based on the combination of ideas from different psychological directions, paying attention to the issues of manifestation of the potential of the person, activation of internal resources and their interconnection. Positive psychotherapy as a method offers tools for identifying and reinterpreting resources. Today, when the uncertainty of the external world, socio-cultural changes and various stressors deeply affect the psyche of the individual, the problem of psychological resources becomes an urgent and purposeful subject of discussion. In this regard, the conscious development and use of resources can significantly contribute not only to maintaining mental stability, but also to effective social adaptation, professional stability and improvement of the quality of life.